UJI KELAYAKAN E-MODUL DENGAN MENGGUNAKAN APLIKASI SIGIL PADA MATERI FENOMENA KUANTUM KELAS XII SMA - Rahmah, Novriani; Azizahwati, Azizahwati; Sahal, Muhammad (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2023)
Abstract The research was conducted to obtain products in the form of e-modules with the E-PUB format which were made using the sigil application on quantum phenomena material for class XII SMA. E-module with sigil application supports text, images, audio and video. This e-module learns about black body radiation, photoelectric effect, Compton effect and x-ray. The research method adopted the Research and Development (R&D) method with the ADDIE model. The ADDIE model is divided into five stages, namely analysis, design, development, implementation and evaluation. This research was conducted from the analysis, design to development stages. The data source was obtained from the scores of the questionnaire assessment results in the form of a checklist filled in by 3 expert validators. There are 4 aspects of the assessment carried out by the validator, namely aspects of content feasibility, linguistic aspects, presentation aspects and graphical aspects. The data obtained shows that the content feasibility aspect gets a score of 3.55 getting a very high category, the linguistic aspect has a score of 3.49 getting a high category, the presentation aspect has a score of 3.66 getting a very high category, and the graphical aspect has a score of 3.33 getting high category. So that the total average score of all aspects is 3.51 with a very high category. The conclusion from this study is that the e-module using the sigil application on quantum phenomena material for class XII SMA is valid and feasible to carry out for further research, namely the field trial stage, namely the implementation stage.